(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The alienation of the most challenging human phenomena, especially in our time, and those who fear its effects and reflections and who considers it a concept that may have the meanings of inevitability and coercion as a human behavior is inevitable, tarnish concepts and ideas and may indeed be a challenge on the levels of knowledge and abstract and realistic The concept of alienation between the two dimensions of general abstract knowledge or the so-called epistemological dimension and social dimension. Or knowledge related to the field of sociology, which is more discussion and treatment being a concept of epistemological sociological at the same time. Keywords- Alienation, epistemological analysis, sociological analysis, educational alienation, Family alienation, political alienation